Information, Beliefs, and Ways of Knowing in the Post-Truth Era - Oliphant, Tami (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2018)
In 2016, Oxford Dictionaries claimed “post-truth” as word of the year. Post-truth is the supremacy of belief, emotion, and worldviews over information and facts. While post-truth is nothing new, it invites reconsideration of information, disinformation, misinformation, and knowledge from an understudied perspective: the internal conditions and different ways of knowing that shape and influence information interactions. This conceptual paper explores the relationships among beliefs, emotion, and faith, internal conditions, information, and different ways of knowing by drawing upon two recent events: the preventable death of a toddler and the fundamental belief system change of a white supremacist.